The oretical basis and operative difficulties of whole-course membrane anatomy in laparoscopic low rectal cancer surgery - Shi Yunjie; Wang Hao (结直肠肛门外科)
Total mesorectal excision (TME) is the “golden standard” that must be followed in laparoscopic surgery for low rectal cancer. Adhering to the surgical concept of “membrane anatomy” is the foundation for achieving TME in low rectal cancer. Our team advocates the surgical separation of “whole-course membrane anatomy” for low rectal cancer, with the surgical dissection always maintained in the “holy plane” between the visceral and parietal fasciae of the organs, which ensures the standardization and radicality of the surgery. Following the principle of “whole-course membrane anatomy” surgical separation can reduce intraoperative and postoperative complications and ensure the effect of tumor radical resection. This article discusses hotspots and difficulties such as the dissection of 253 lymph node groups, freedom of the splenic flexure of the colon, membrane anatomy and nerve protection in the perirectal space, extreme sphincter-preserving surgery for very low rectal cancer, and other surgical related issues that require special attention during surgery in laparoscopic low rectal cancer surgery.